The rise in women's labour force participation in Mexico: Supply vs demand factors - Sonia R. Bhalotra; Manuel Fernández (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We estimate the relative importance of alternative labour supply and demand mechanisms in explaining the rise of female labour force participation over the last 55 years in Mexico. The growth of female labour force participation in Mexico between 1960 and 2015 followed an S-shape, with a considerable acceleration during the 1990s. Using decomposition methods and a shift-share design, we show that, put together, supply and demand factors can account for the rise of female labour force participation over the period, led by increases in women's education and shifts in the occupational structure of the workforce. However, there is unexplained variation in the 1990s, when female labour force participation spiked.
Keywords: J16; J21; J22; J23; 330; female labour force participation; Mexico; education; labour demand; labour supply